Analisis Bagi Hasil Akad Mudharabah Pada Bank Syariah Dalam Implementasi Produk Tabungan Berdasarkan Fatwa DSN No: 02/DSN-MUI/IV/2000 - Andriyansah (Falah: Jurnal Hukum Ekonomi Syariah, 2021)
This research is a qualitative research method, which describes and explains profit sharing on savings products using mudharabah contracts at PT. BPR Syariah Way Kanan, which was obtained from data and information through documentation, interviews and direct observation to the bank. The techniques in research analysis used are data reduction, data presentation, drawing conclusions or verification. By using this research method, it can be found that the application of profit sharing to savings products that use mudharabah contracts is in accordance with the provisions of the Fatwa of DSN MUI NO: 02/DSN-MUI/IV/2000. The results show that PT. BPR Syariah Way Kanan does not apply the interest system because the interest system is considered part of usury and is haram in Islam. Profit sharing obtained from the mudharabah contract savings product at PT. BPR Syariah Way Kanan generally offers a profit-sharing ratio with a percentage of 60:40, but if the profit-sharing increases, the profits will be high, but if the profit-sharing falls, the profits will be low.